From litter decomposition to soil organic matter formation: using stable isotopes to determine the fate of carbon and nitrogen - Horton, Andrew James, author; Cotrufo, M. Francesca, advisor; von Fischer, Joseph, committee member; Paschke, Mark, committee member (Colorado State University. Libraries, 2014)
Litter decomposition releases the energy and nutrients fixed during photosynthesis into the atmosphere and soil. In the soil, carbon and nitrogen from the litter can be stabilized in soil organic matter pools, which globally represent large pools of both carbon (C) and nitrogen (N). Soil organic matter pools are heterogeneous, the product of different stabilization processes and will stabilize C and N for periods of time ranging from years to millennia. A thorough mechanistic understanding of the fate of above-ground litter C and N is essential to understand how climate change could affect both carbon sequestration and soil health. This research studied the fate of litter derived organic matter. Isotopically labeled litter was used in a field incubation to trace litter derived C and N into different SOM pools and soil depths over the course of 3 years. Additionally, naphthalene was used to suppress microarthropods to determine the impact of mesofauna on the fate of litter derived N. In the laboratory, soil from the field experiment was incubated for 150 to determine how different SOM pools contributed to respiration and leaching. Microarthropods do not increase overall N mineralization rates, but do influence the fate of litter derived N. When present, microarthropods increased the amount of litter derived N in the light fractions, suggesting that microarthropods increase litter fragmentation. Surprisingly, litter derived organic matter does not contribute to respiration and leaching equally, suggesting that leaching and respiration are not directly related. Litter derived OM behaves differently than older OM present in the soil, with the newer litter derived C and N being more readily lost from SOM pools. This result supports the onion layering model suggested by Sollins (Sollins et al. 2006). In order to create more accurate models, microarthropods and the onion layering model should be included in future C and N dynamic studies.
Keywords: 13C & 15N stable isotopes; tallgrass prairie; soil organic matter; microarthropods; litter decomposition